2019
DOI: 10.1109/access.2019.2918552
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Guidelines for Requirements Change Management in Global Software Development: Client-Vendor Perspective

Abstract: Currently, being deployed by organizations to develop high-quality software at a low cost, global software development (GSD) faces many challenges that make development activities more complex. These GSD challenges are mainly concerned with requirements to change management (RCM). RCM plays a key role in the successful execution of software projects. The objective of this paper is to identify the best practices of the RCM process by adopting a systematic literature review (SLR) and validate them using question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 38 publications
0
50
0
Order By: Relevance
“…Furthermore, Kumar and Kumar and Lai and Ali reported that the cultural and language conflicts in such distributed environments can negatively affect team members' understanding of the requirements change process. The above discussion shows that limited research has been conducted to highlight the significance of RCM programs in GSD environments and to develop specific models/frameworks for managing RCM activities . This research gap motivates us to develop an RCM process maturity model that can guide GSD organizations toward the successful deployment of their change management activities.…”
Section: Research Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, Kumar and Kumar and Lai and Ali reported that the cultural and language conflicts in such distributed environments can negatively affect team members' understanding of the requirements change process. The above discussion shows that limited research has been conducted to highlight the significance of RCM programs in GSD environments and to develop specific models/frameworks for managing RCM activities . This research gap motivates us to develop an RCM process maturity model that can guide GSD organizations toward the successful deployment of their change management activities.…”
Section: Research Motivationmentioning
confidence: 99%
“…This maturity model is based on the concepts and understanding of the available models in other software engineering domains . We discussed the preliminary results of this study in our published research articles . The proposal for this study was also accepted as a paper for the ACM/SIGAPP research competition, where the maturity model was presented in a PhD research competition .…”
Section: Research Motivationmentioning
confidence: 99%
See 3 more Smart Citations